Sustainable Earthen Construction: A Meta-Analytical Review of Environmental, Mechanical, and Thermal Performance - Viviana Mora-Ruiz; Jonathan Soto-Paz; Shady Attia; Cristian Mejía-Parada (Buildings)
This study examines the main earthen constructions—such as adobe, compressed earth blocks (CEBs), and rammed earth walls (REWs)—highlighting their potential to reduce the environmental impact compared to conventional materials. Through a systematic literature review (2013–2024) and a meta-analysis, the mechanical, thermal, and sustainability properties of these constructions are analyzed. Emphasis is placed on the use of additives, such as stabilizers and fibers from various industrial and agro-industrial by-products, as leading actors influencing the mechanical and environmental performance of earthen constructions (EnCs). Remarkable improvements in the compressive and flexural strength are found, especially in stabilized CEBs and REWs, where strengths of up to 24 MPa are reached in certain mixtures, comparable to conventional materials such as concrete. However, the impact of these admixtures on environmental aspects, as measured through metrics such as the global warming potential (GWP), remains poorly documented. This review also shows that numerical methods like finite element modeling (FEM) have been crucial to modeling and predicting the performance of these materials, contributing to the understanding of their dynamic and structural responses. The findings suggest that, although CEB is currently the most studied onshore technique, future challenges include the standardization of admixtures and regulation of sustainable practices globally.